The use of telephone interviews in qualitative psychology research: A reflective methodological exercise - Kassianos, Angelos P. (My University, 2014)
There is little evidence on how telephone interviews are used in qualitative psychological research compared to face-to-face interviews. This reflective methodological exercise explores the use of telephone interviews as a method in relation to interviewing prostate cancer patients about their dietary changes in a recent study. In conclusion, both methods of collecting data are qualitatively different and can offer a range of advantages. The decision must be based on the aims of the study, the population studied, the interviewer’s experience and the decisive balance between cost-effectiveness and wider demographics on the one hand and richer data on the other.
Keywords: Telephone interviews; Cancer patients; Risk of losing information